Suplementasi obat cacing, sirup Fe, dan vitamin C meningkatkankadar hemoglobin dan status gizi balita di Kupang - Siti Romlah; Hamam Hadi; M. Juffrie (Alma Ata University Press, 2013)
ABSTRACTBackground: The prevalence of having intestinal worms among malnourished children under ﬁ ve as the cause of anemia at the Province of Nusa Tenggara Timur is still relatively high. Efforts to minimize intestinal worm infection and anemia and to increase nutrition status of malnourished children under ﬁ ve who get recovery complementary foods are made through supply of intestinal worm drugs, Fe syrup and vitamin C.Objective: To identify the effect of the supply of intestinal worm drugs, Fe syrup, and vitamin C supplementation to the increase of haemoglobin (Hb) level and nutritional status of malnourished children under ﬁ ve who got recovery complementary foods.Method: This was an experimental study with factorial design. Subject of the study were malnourished children under ﬁ ve of 1–3 years of age at Kupang Municipality. There were as many as 128 samples divided into 4 experiment groups. The group got pyrantel pamoat intestinal worm drugs 125 mg (n=32), Fe syrup + vitamin C (n=32), and placebo (n=32). Hb level was measured using “Hemocue-B Hemoglobin photometer”, intestinal worm infection was observed through facces of the subject to identify the presence of worm eggs. Statistical analysis used t-test to identify the relationship before and after the supply and ANOVA to ﬁ nd out the difference in the effect of the supply among the groups. Result: After 3 months, the supply of the intestinal worm drugs before intervention had signiﬁ cant effect to intestinal worm infection status among the group with intestinal worm drugs and the group with intestinal worm drugs, Fe syrup + vitamin C. The highest increase of Hb level was found in the group with intestinal worm drugs, Fe syrup + Vitamin C with average increase as much as 1.2 g/dL. Average increase of weight among the groups was 0.3 kg. Increase ofZ-score signiﬁ cantly affected index of weight/age and weight/height.Conclusion: The increase of Hb level signiﬁ cantly affected changes of nutritional status increase among the experiment groups.KEYWORDS: intestinal worm drugs, Fe syrup, vitamin C, Hb level, nutritional status, malnourishmentABSTRAKLatar Belakang: Prevalensi kecacingan pada balita gizi buruk sebagai penyebab anemia di Provinsi NTT masih tinggi. Upaya menurunkan infeksi kecacingan dan anemia serta meningkatkan status gizi pada balita gizi buruk yang mendapat PMT-P antara lain dengan pemberian obat cacing dan suplementasi sirup Fe + vitamin C.Tujuan: Mengetahui pengaruh pemberian obat cacing, suplemen sirup Fe, dan vitamin C terhadap peningkatan kadar Hb dan status gizi balita gizi buruk penerima PMT-P.Metode: Jenis penelitian adalah eksperimental dengan rancangan faktorial. Sasaran penelitian adalah balita gizi buruk usia 1–3 tahun di Kota Kupang. Jumlah sampel sebanyak 128 anak dibagi dalam 4 kelompok perlakuan. Perlakuan obat cacing pirantel pamoat 125 mg (n=32), sirup Fe + vitamin C (n=32), obat cacing, sirup Fe+ vitamin C (n=32) dan plasebo (n=32). Pengukuran kadar hemoglobin dengan ”HemoCue”, infeksi cacing diperiksa melalui tinja subjek untuk melihat adanya telur cacing. Analisis menggunakan uji T-test untuk mengetahui hubungan sebelum dan sesudah suplementasi dan uji ANOVA untuk melihat perbedaan efek suplementasi antar kelompok. Hasil: Setelah 3 bulan, pemberian obat cacing sebelum intervensi berpengaruh signiﬁ kan terhadap status infeksi kecacingan pada kelompok obat cacing dan kelompok obat cacing, sirup Fe + vitamin C. Peningkatan kadar hemoglobin antarkelompok yang tertinggi adalah pada kelompok obat cacing, sirup Fe dan vitamin C dengan ratarata kenaikan sebesar 1,2 g/dL. Rata-rata kenaikan berat badan antar kelompok sebesar 0,3 kg. Peningkatan nilai Z-score berpengaruh signiﬁ kan terhadap indek BB/U dan BB/TB.Kesimpulan:Peningkatkan kadar hemoglobin berpengaruh signiﬁkan terhadap perubahan peningkatan status gizi antar kelompok suplementasi.KATA KUNCI: obat cacing, sirup Fe +vitamin C, kadar hemoglobin, Z-score, status gizi